Comprehensive in vitro and in vivo evaluation of therapeutic potential of Bacopa-derived asiatic acid against a human oral pathogen Streptococcus mutans - Jeyasri, Rajendran; Muthuramalingam, Pandiyan; Priya, Arumugam; Alexpandi, Rajaiah; Shanmugam, N. R. Siva; Nivetha, Saminathan; Shin, Hyunsuk; Pandian, Shunmugiah Karutha; Ravi, Arumugam Veera; Ramesh, Manikandan (Frontiers in Microbiology, 2024)
Dental caries is a common human oral disease worldwide, caused by an acid-producing bacteria called Streptococcus mutans. The use of synthetic drugs and antibiotics to prevent dental caries has been increasing, but this can lead to severe side effects. To solve this issue, developing and developed countries are turning to herbal medicines as an alternative to synthetic drugs for the treatment and prevention of dental caries. Therefore, there is an urgent need for plant derived products to treat such diseases. Bacopa monnieri, a well-documented medicinal plant, contains 52 phytocompounds, including the pentacyclic triterpenoid metabolite known as Asiatic acid (ASTA). Hence, this study aimed to demonstrate, for the first time, the antibacterial activity of phytocompound ASTA against S. mutans. The findings revealed that ASTA significantly inhibited the growth of S. mutans and the production of virulence factors such as acidurity, acidogenicity, and eDNA synthesis. Molecular docking analysis evaluated the potential activity of ASTA against S. mutans virulence genes, including vicR and gtfC. Furthermore, a toxicity assessment of ASTA in human buccal epithelial cells was performed, and no morphological changes were observed. In vivo analysis using Danio rerio (zebrafish) confirmed that ASTA treatment significantly increased the survival rates of infected fish by hindering the intestinal colonization of S. mutans. Further, the disease protection potential of ASTA against the pathognomonic sign of S. mutans infection was proved by histopathological examination of the gills, gut, and kidney. Overall, these findings suggest that ASTA may be a promising therapeutic and alternative drug for the treatment and prevention of oral infection imposed by S. mutans.